Scolopsis meridiana, a new species of monocle bream (Perciformes: Nemipteridae) from northern Australia - Nakamura, Jumpei; Russell, Barry C.; Moore, Glenn I.; Motomura, Hiroyuki (Zootaxa, 2018)
Scolopsis meridiana n. sp., described from 30 specimens collected from northern Australia, is closely related to S. taenioptera, both species having a dorsal scaled area on the head extending anteriorly to between the anterior margin of the eye and anterior nostril, the upper part of the pectoral-fin base with a reddish blotch when fresh, and lacking a small antrorse spine below the eye. However, the new species is distinguished from the latter by having two bands across the snout dorsum (vs. one band in S. taenioptera), 18–20 diagonal lines on the lateral body surface below the lateral line (diagonal lines absent), the posterior nostril horizontally elongated (vertically elongated), a deep caudal-peduncle and short pre-dorsal-fin length. Scolopsis meridiana is distributed in northern Australia, whereas S. taenioptera occurs in Southeast Asia. Two geographic populations of S. taenioptera (Philippines and remaining Southeast Asian region) are recognized following morphological and genetic analyses.